Legal Aspects of the Concept of a Brand with a Domain Name of Intellectual Property - Nurpalah, Nurpalah; Senjaya, Oci (Jurnal Independent, 2023)
This is a problem in itself considering that domain names, which technically function as online identifiers used to make it easier to find certain locations in cyberspace, are often associated with brands that are actually business identifiers in the real world. The purpose of this study is to determine the linkage, protection, and settlement for brand owners whose brands are registered as domain names by other parties in the context of Indonesian law. The method used in this research is a normative legal research method with a statutory, case, and concept approach. However, the result of this research is that brands and domain names have a common function as a "differentiator" of a product or business, especially in cyberspace, there are significant differences from the legal constructions that govern them. Domain names are only protected by law if they are registered with the Directorate General of Intellectual Property Rights (Ditjen HKI) as a trademark in accordance with Law No. 15 of 2001 concerning Trademarks, besides that the form of legal protection is also contained in the Law on ITE. Meanwhile, dispute resolution of domain names of well-known brands on the internet can be done through the Indonesian Internet Domain Name Manager (PANDI), as well as the implementation of dispute resolution in the Arbitration and Dispute Resolution Law, the Electronic Information and Transaction Law, as well as the Trademark Law, and other international rules that contain domain names.